Optimization of seed and seedling production in Hempedu Bumi (Andrographis paniculata (Burm.f.) Wall. ex Nees) - Wong, Kian Joo (2016)
The propagation of Andrographis paniculata is generally through seed but the germination is poor due to seed dormancy. Therefore, seven seed dormancy breaking treatments namely water soaking for 24 hours, sand paper scarification, hot water soaking at 40°C for 10 minutes, hot water soaking at 50°C for 10 minutes, hot water soaking at 60°C for 5 minutes and combination of sand paper scarification, hot water soaking (60°C for 5 minutes) and a control were investigated to determine the best seed dormancy breaking treatments. The percentage of seed germination scarified using sand paper was 91%. Seeds took the shortest time of 3.5 days to reach 50 % germination after scarified and followed with hot water soaking at 60°C for 5 minutes. Maturity at harvest and storage are important that will affect the seed quality. Currently no study has been carried out to study the effect of maturity and storage on seed quality dan germination. The effects of two maturity stages (grey purple capsule and grey brown capsule) and four storage periods (0, 3, 6 and 9 months) with and without sand paper scarification were investigated to determine the seed germinability. Freshly harvested seeds from grey brown capsule had lower 1000 seed weight, lower seed moisture and higher seed dry matter of 1 gram seed compared to seeds from grey purple capsules. However, maturity stage and storage period did not affect 1000 seed weight, seed moisture and seed dry matter of 1 gram seed after the capsules were slow dried in desiccator. Germination percentage was recorded higher for seeds from grey brown capsule rather than grey purple capsule. Germination improved after 6 months of storage without scarification. None of the untreated seeds from different maturity stages and storage periods had more than 50 % germination. Seeds from grey brown capsule reached 50 % germination faster than seeds from grey purple capsule. Time to 50 % germination was significantly reduced after 6 months of storage. The effects of three seedling tray cell volume (43 cm3, 30 cm3 and 25 cm3) and seven growing media (mixed soil, cocopeat, 4 cocopeat : 1 rice husk biochar, 3 cocopeat : 2 rice husk biochar, 4 cocopeat : 1 EFB compost, 3 cocopeat : 2 EFB compost and 4 cocopeat : 3 rice husk biochar : 3 EFB compost) were investigated to determine a suitable growing media and seedling tray for the production of organically grown seedlings A. paniculata. Seedling height, fresh weight, total leaf area and dry weight were increased when the cell volume increased from 43 cm3 to 30 cm3 then reduced at cell with 25 cm3. Root shoot ratio did not differ significantly between seedling tray cell volumes. Root length and root volume increased significantly when the number of cell in tray increased. Seedlings grown in media cocopeat : biochar : EFB compost in ratio 4:3:3 (CBE) had the highest seedling height, fresh weight, total leaf area, dry weight, root length and root volume. There were significant interaction effects between seedling tray cell volume and growing media on seedling height, fresh weight, total leaf area, root length and root volume. Quality seedlings can be obtained in cell with 30 cm3 with media CBE. Light duration is one of the environmental factors important that can influence flowering, seed fertility and seed production. However, no photoperiodic treatments has been studied for this plant. Therefore, the effects of four short day treatments (12 hours, 10 hours, 8 hours and 6 hours) was investigated to determine the suitable short day treatment for seed production. Plant height increased significantly when the day length provided becomes shorter. Short day treatments did not affect secondary branches and dry weight of plants. The heaviest plants of 172.70 g in fresh weight were grown in 6 hours day length. Prolonged days to flowering and days to mature capsule formation were observed when day length was reduced from 12 hours to 6 hours. A. paniculata grown in 12 hours (control) recorded the highest number of flower of 459.50, number of capsule of 359.67 and harvest index of 9.78 % respectively. The highest 1000 seed weight of 0.146 g was recorded from the plants grown in 12 hours. However, short day treatments did not influence the seed moisture content, seed dry matter of 1 gram seed and seed germinability. It is recommended that the seedling and seed production of A. paniculata can optimized by planting sand paper scarified seeds from grey brown capsule on combination media of cocopeat:biochar:EFB compost in 30 cm3 seedling tray. A. paniculata is not a short day plants.